Global trends in educational environment design: From cultural dimensions to innovations - Vezhbovska, Liliana; Boltenkov, Arkadii; Vaskialite, Valentyna; Lopukhova, Natalya; Dementovych, Tetiana (Research Journal in Advanced Humanities, 2024)
This study aimed to examine global trends in educational environment design, concentrating on the shift from cultural dimensions to innovative strategies. The goal was to provide a comprehensive understanding of the factors influencing the evolution of learning spaces. Our research methodology focused on a multi-case study approach, evaluating outstanding educational environments from various cultural and geographical backgrounds. Architectural blueprints and design documents were analyzed to gain insights into the creative processes behind these designs. Furthermore, we conducted a comparative analysis of international best practices in educational space design, emphasizing the role of culture and innovation in molding contemporary educational settings. This approach facilitated a detailed exploration of the key trends and their impact on learning experiences. The analysis revealed that integrating cultural dimensions and innovative systems in educational environment design results in flexible, inclusive, and adaptive learning spaces. The study also highlighted a growing focus on technology, collaboration, and sustainable design principles in shaping modern educational environments, mirroring the evolving needs of students and educators. These findings have substantial implications for educators, policymakers, and designers, as they underscore the importance of considering cultural dimensions and innovative methods when developing educational environments. By integrating these elements, academic institutions can create learning spaces that nurture creativity, collaboration, and personalization, ultimately enhancing student engagement and learning outcomes.